Understanding the physical state of hot plasma formed through stellar wind collision in WR140 using high-resolution X-ray spectroscopy. Issue 4 (10th May 2022) - Miyamoto, Asca; Sugawara, Yasuharu; Maeda, Yoshitomo; Ishida, Manabu; Hamaguchi, Kenji; Corcoran, Michael; Russell, Christopher M P; Moffat, Anthony F J
ABSTRACT: We analyse a series of XMM–Newton RGS data of the binary Wolf–Rayet star WR140 that encompasses one entire orbit. We find that the RGS detects X-rays from optically thin thermal plasma only during orbital phases when the companion O star is on the near side of the WR star. Although such X-rays are believed to be emitted from the shock cone formed through collision of the stellar winds, temperature and density profiles of the plasma along the cone have not been measured observationally. We find that the temperature of the plasma producing Ne emission lines is 0.4–0.8 keV, using the intensity ratio of Kα lines from He-like and H-like Ne. We also find, at orbital phases 0.816 and 0.912, that the electron number density in the Ne line-emission site is approximately 10 12 cm −3 from the observed intensity ratios f / r and i / r of the He-like triplet. We calculated the shock cone shape analytically, and identify the distance of the Ne line-emission site from the shock stagnation point to be 0.9–8.9 × 10 13 cm using the observed ratio of the line-of-sight velocity and its dispersion. This means that we will be able to obtain the temperature and density profiles along the shock cone with emission lines from other elements. We find that the photoexcitation rate by the O star is only 1.3–16.4 per cent of that of the collisional excitation at orbital phase 0.816. This implies that our assumption that the plasma is collisionally excited is reasonable, at least at this orbital phase.